Temporomandibular joint pain and associated magnetic resonance findings: a retrospective study with a control group. (September 2020) - Eriksen, Elisabeth Schilbred; Hellem, Sølve; Skartveit, Liv; Brun, Johan G; Bøe, Olav E; Moen, Ketil; Geitung, Jonn Terje
Background: To better understand and evaluate clinical usefulness of magnetic resonance imaging (MRI) in diagnosis and treatment of temporomandibular disorders (TMD), parameters for the evaluation are useful. Purpose: To assess a clinically suitable staging system for evaluation of MRI of the temporomandibular joint (TMJ) and correlate the findings with age and some clinical symptoms of the TMJ. Material and Methods: Retrospective analysis of 79 consecutive patients with clinical temporomandibular disorder or diagnosed inflammatory arthritis. Twenty-six healthy volunteers were included as controls. Existing data included TMJ pain, limited mouth opening (<30 mm) and corresponding MRI evaluations of the TMJs. Results: The patients with clinical TMD complaints had statistically significantly more anterior disc displacement (ADD), disc deformation, caput flattening, surface destructions, osteophytes, and caput edema diagnosed by MRI compared to the controls. Among the arthritis patients, ADD, effusion, caput flattening, surface destructions, osteophytes, and caput edema were significantly more prevalent compared to the healthy volunteers. In the control group, disc deformation and presence of osteophytes significantly increased with age, and a borderline significance was found for ADD and surface destructions on the condylar head. No statistically significant associations were found between investigated clinical and MRI parameters. Conclusion: This study presents a clinically suitable staging system for comparable MRI findings in the TMJs. Our results indicate that some findings are due to age-related degenerative changes rather than pathological changes. Results also show that clinical findings such as pain and limited mouth opening may not be related to changes diagnosed by MRI.